Identification and function of an evolutionarily conserved signaling intermediate in Toll pathways (ECSIT) from Crassostrea hongkongensis. Issue 1 (November 2015) - Qu, Fufa; Xiang, Zhiming; Wang, Fuxuan; Zhang, Yang; Li, Jun; Zhang, Yuehuan; Xiao, Shu; Yu, Ziniu
Abstract Evolutionarily conserved signaling intermediate in Toll pathways (ECSIT) is a multifunctional adaptor protein that plays a key role in the regulation of the oxidative phosphorylation (OXPHOS) system, bone morphogenetic protein (BMP) pathway and Toll-like receptor (TLR) signaling pathway in mammals. However, the function of ECSIT homologs in mollusks, the second most diverse group of animals, is not well understood. In this study, we identified an ECSIT homolog in the Hong Kong oyster Crassostrea hongkongensis (ChECSIT) and investigated its biological functions. The full-length cDNA of ChECSIT is 1734 bp and includes an open reading frame (ORF) of 1074 bp that encodes a polypeptide of 451 amino acids. The predicted ChECSIT protein shares similar structural characteristics with other known ECSIT family proteins. Quantitative real-time PCR analysis revealed that ChECSIT mRNA is broadly expressed in all of the examined tissues and at different stages of embryonic development; its transcript level could be significantly up-regulated by challenge with microorganisms (Vibrio alginolyticus, Staphylococcus haemolyticus and Saccharomyces cerevisiae). In addition, ChECSIT was found to be located primarily in the cytoplasm, and its overexpression stimulated the transcriptional activity of an NF-κB reporter gene in HEK293T cells. These findings suggest that ChECSIT might be involved in embryogenesis processes and immune responses in C. hongkongensis.